Juridical Analysis Of Court Decision Number 542/Pdt.P/2023/Pn.Smg Concerning Guardianship Of Minors For Inheritance Of Shares - Hendricus Andrianto; Setiyowati Setiyowati; Aniek Tyaswati Wiji Lestari (International Journal of Law, Crime and Justice, 2024)
This research examined the rationale behind guardianship stipulations for minors and aspects of inheritance law in Indonesia, particularly concerning the inheritance of shares to children. Through an analysis of the Semarang District Court Decree Number 542/PDT.P/2023/PN.SMG, which stipulates that the petitioner, as the biological father of his children, must still obtain a legally valid and legitimate guardianship stipulation from the court. This study used a normative juridical method with a descriptive-analytical approach, aimed at understanding the legal considerations of judges in determining guardianship and its juridical implications on children's rights. The research findings indicate that court-determined guardianship is a crucial step in providing legal certainty and protecting children's rights in shared inheritance. The juridical implications of such stipulations include legitimizing the guardian's actions, oversight against abuse of power, protection of the child's assets, and management of shareholder rights in companies. This study concludes that court-determined guardianship is a critical instrument in ensuring legal protection for minors in the context of shared inheritance.